Clinical suspicion of sarcopenic obesity and probable sarcopenic obesity in Colombian women with a history of surgical menopause: a cross-sectional study (2022)
Objectives: To identify the frequency of clinical suspicion of sarcopenic obesity (CSSO) and probable sarcopenic obesity (PSO) and to estimate the association between them and surgical menopause. Methods: A cross-sectional study carried outin women residing in Colombia, ages 60to 75 years. Body mass index, the SARC-F scale, SARC-CalF< 31, and SARC-CalF <33 versions adding the calf circumference measurement in the last two were used to identify CSSO. Muscle strength measurement was added to the above measures to establish PSO. Surgical menopause was defined in women who underwent bilateral oophorectomy simultaneously with hysterectomy before natural menopause. Adjusted and unadjusted logistic regression were performed between CSSO or PSO with surgical menopause, bilateral oophorectomy after natural menopause, and abdominal hysterectomy with ovarian preservation. All participants provided informed consent. P < 0.05 was statistically significant. Results: Seven hundred women 67.0 4.8 years old were included; 23.7% were obese, 68.1% had reduced muscle strength, and 4.2% had surgical menopause. CSSO was found in 3.0% with SARC-F and with SARC-CalF < 31; whereas 2.0% were found with SARC-CalF <33. PSO was found in 2.4%, 1.5%, and 2.2% with SARC-F, SARC-CalF <31, and SARC-CalF <33, respectively. Surgical menopause was associated with PSO but was not associated with CSSO. Bilateral oophorectomy after menopause and hysterectomy with ovarian preservation were not associated with CSSO or PSO. Conclusions: In a group of older adult women, the frequency of CSSO was up to 3.0% and PSO up to 2.4%. Surgical menopause was statistically significantly associated with PSO. On the contrary, CSSO was not associated.